Skills Acquired and Passed on: The Collaboration between the University of Bergen and Makerere University Libraries and their New Partners in the North and South - Landoy, Ane; Musoke, Maria G. N. (Makerere University, 2009)
Makerere University in Uganda and the University of Bergen in Norway celebrate ten years of collaboration in 2009. The collaboration includes the libraries in the two Universities, focusing on continuing professional development. This paper reports the activities of the collaboration between the two University libraries, and highlights the multiplier effect of the collaboration, which has led to new partners at the University of Juba in Southern Sudan, the East African School of Library and Information Science (EASLIS) at Makerere and the Norwegian School of Librarianship at Oslo University College. The new partners have joined to implement the Juba University Library Automation Project (JULAP) that is funded by the Norwegian Ministry of Foreign Affairs. JULAP aims to rebuild the Juba University Library that was closed because of the war in 1985. The project has two main components: automation of the library and training of library staff who are already working in the library, as well as sponsoring young people for a Bachelor’s degree in Librarianship at EASLIS. The training of library staff has a theoretical component conducted by EASLIS, while the practical component is handled by Makerere University Library staff using the skills they acquired over time from collaborations with skilled librarians from the North. Part of the project includes the acquisition of a library system, and the training of staff to use the system. The paper then outlines the activities of the project, the challenges faced and how they have been addressed, the achievements and future plans. Although most collaboration usually involves two institutions, this paper highlights the growth of the collaboration from two institutions to where it is now, and the audience is encouraged to learn from this experience and replicate it to be able to ‘build bridges’ of LIS education in Developing countries.
Keywords: Skills; University of Bergen; Makerere University Libraries